HLA as risk and protection antigens against urinary tract diseases - M. Kolesnyk; S. Vozianov; V. Driianska; O. Shulyak; I. Gorpynchenko; Yu. Bondarenko; M. Velychko; I. Petrina; V. Chernenko; D. Chernenko; T. Poroshina; K. Nurimanov (Ukrainian Journal of Nephrology and Dialysis, 2022)
Abstract. Currently, there is no doubt about the feasibility of determining the frequency of HLA and analysis of genetic associations, including those that determine the state of immunity, in patients with the genitourinary disease.The study aimed to evaluate HLA phenotypes in patients with the most common diseases of the genitourinary system and identify risk antigens or protectors.Methods. HLA distribution was studied in 384 patients with pyelonephritis and glomerulonephritis and 464 patients with urological diseases (chronic cystitis, chronic proliferative cystitis, chronic prostatitis, prostate sclerosis, prostatic hyperplasia, and prostate cancer). HLAs were defined using a standard microlymphocytotoxic test (Terasaki’s test) on the Terasakiґs planchette with panels of anti-HLA serums (20 antigens of locus A, 31 – B and 9 – DR). The control group consisted of 350 healthy donors from Ukraine.The HLA frequencies in healthy and diseased subjects were compared taking each antigen separately, using the χ2  test. The value of the relative risk of disease (RR) was determined by the coefficient: RR = ab/cd, where a is the number of patients positive for this antigen, b is the number of persons in control, negative for this antigen; c is the number of patients negative for this antigen, d is the number of persons in control positive for this antigen. Indicators RR≥ 2.0 were considered significant.Absolute (attributive) risk of the disease as an etiological fraction, which was determined by the formula: s = x - y/1 - y, where x is the frequency of antigen in patients, y is the frequency in healthy people. The indicator s> 0,1 was considered reliable.Results. The association of the most common genitourinary diseases with certain histocompatibility antigens (RR≥2) is shown. The causal role of HLA with a significant absolute risk of pyelonephritis (А10, А11; В14, В16) and glomerulonephritis (A24, А28; B8; DR4, DR52), chronic cystitis, (including proliferative) (A10, B14, B16), chronic prostatitis (including with an autoimmune component or impaired fertility) (А24, В8, В52), sclerosis of the prostate (А24, А28), hyperplasia (А29, В38) and prostate cancer (А25, А29, В40, В44, В49) has been established. HLA-antigens associated with protection against these pathologies have also been identified - А2, А24, В21, В35 for pyelonephritis and А9, В12, В16, В18 for glomerulonephritis; А25, А26, В5, В14, В16, В17 for chronic prostatitis with its complications,  А10, B15, B17 for prostate sclerosis, А9, А10, В17 for prostate hyperplasia, A1, B5, B13, B15 for prostate cancer.Conclusion. The study proves the feasibility of identifying antigens of the HLA system and analysis of their associations with different genitourinary diseases, which allows for predicting the risks of the disease and treatment optimization.